Hegemony of Gender Ideology Through Hyperbody of Indonesian Artificial Intelligence - Agustin, Sari Monik (Universitas Prof. Dr. Moestopo (Beragama), 2024)
Some time ago, Indonesia was amazed by the presence of a female celebrity named